2019
DOI: 10.1101/cshperspect.a034660
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Development and Perspectives toward Agricultural Improvement

Abstract: Stomata are small pores on the surface of land plants that facilitate gas exchange-acquiring CO 2 from surrounding atmosphere and releasing water vapor. In adverse conditions, such as drought, stomata close to minimize water loss. The activities of stomata are vital for plant growth and survival. In the last two decades, key players for stomatal development have been discovered thanks to the model plant Arabidopsis thaliana. Our knowledge about the formation of stomata and their response to environmental chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 131 publications
(225 reference statements)
1
24
0
Order By: Relevance
“…For most plant species, including Arabidopsis and grasses, the stomatal lineage progresses in much the same way; originating from a set of undifferentiated epidermal cells at the base of the leaf known as protodermal cells (Stebbins and Shah, 1960;Yang et al, 1995;Luo et al, 2012;Pillitteri and Dong, 2013;Raissig et al, 2016;Hepworth et al, 2018;Endo and Torii, 2019). The stomatal lineage is initiated when individual protodermal cells (known in Arabidopsis as meristemoid mother cells, MMCs) gain the capacity to undergo asymmetric cell divisions ( Figure 1).…”
Section: Grasses Have Conserved and Divergent Elements Of Stomatal Momentioning
confidence: 99%
See 1 more Smart Citation
“…For most plant species, including Arabidopsis and grasses, the stomatal lineage progresses in much the same way; originating from a set of undifferentiated epidermal cells at the base of the leaf known as protodermal cells (Stebbins and Shah, 1960;Yang et al, 1995;Luo et al, 2012;Pillitteri and Dong, 2013;Raissig et al, 2016;Hepworth et al, 2018;Endo and Torii, 2019). The stomatal lineage is initiated when individual protodermal cells (known in Arabidopsis as meristemoid mother cells, MMCs) gain the capacity to undergo asymmetric cell divisions ( Figure 1).…”
Section: Grasses Have Conserved and Divergent Elements Of Stomatal Momentioning
confidence: 99%
“…These bHLHs are known as SPEECHLESS (SPCH), its close paralogues MUTE and FAMA, and SCREAM (SCRM, also known as ICE1) and SCRM2 (Ohashi-Ito and Bergmann, 2006;MacAlister et al, 2007;Pillitteri et al, 2007;Kanaoka et al, 2008) (Figure 2). The formation of MMCs, asymmetric entry divisions and subsequent meristemoid self-renewal requires the first of these, SPCH (Pillitteri and Dong, 2013;Endo and Torii, 2019). MUTE activity is then required to terminate asymmetric divisions and promote the differentiation of meristemoids into GMCs (Pillitteri et al, 2007).…”
Section: Stomatal Lineage Initiation and Advancement Is Governed By Tmentioning
confidence: 99%
“…Notably, the MID3 -Ll-0 allele promotes spacing divisions in a dominant manner, in contrast with the ER repressive role. Multiple studies have addressed how ER negatively regulates SPCH abundance to restrict entry divisions (reviewed in Endo and Torii, 2019), but little is known about its involvement in other processes during stomatal developmental. Lineage arrest in er mutants supports the idea that ER is expressed in SLGCs to buffer the inhibitory activity of EPF1 in the neighboring meristemoid (Qi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The latter are relevant target traits for breeding, whose genetic manipulation through determinants of stomatal development is now pursued. Such manipulations include transgenic approaches and induced mutations that modify stomatal numbers and alter physiological performance (reviewed by Bertolino et al, 2019; Endo and Torii, 2019). However, these studies have shown contrasting effects of stomatal density changes, as higher values do not necessarily correlate with increased stomatal conductance and vice versa (Dittberner et al, 2018; Bertolino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The SLGC, in contrast to the M, has a limited ability to divide and typically differentiates into a non-stomatal pavement cell (PC), which provides protection and structural support for other cell types in the leaf. Stomatal divisions can be responsive to external cues, thus enabling plants to optimize the number and distribution of stomatal pores in response to environmental or developmental changes (Endo and Torii, 2019;Pillitteri and Torii, 2012;Zoulias et al, 2018).…”
Section: Introductionmentioning
confidence: 99%